Innovation and entrepreneurship among health professions students at a medical college in China: a cross-sectional study of attitudes, participation frequency, self-reported competencies, and associated factors - Liyuan Hou; Yuheng Zhang; Yifei Luan (Frontiers in Medicine, 2026)
Introduction This cross-sectional study evaluated innovation and entrepreneurship (I&E) attitudes, participation frequency, and self-reported competencies among 706 undergraduate health professions students at Hangzhou Medical College and examined factors associated with self-reported competency scores. Methods An open, voluntary online survey yielded 723 submissions. After 17 later duplicate submissions were removed by retaining each student’s first response, 706 unique participants were included. A study-specific 5-point questionnaire assessed I&E attitudes (7 items), participation frequency through a single-item behavioral indicator, and self-reported competencies (13 items). Split-sample exploratory and confirmatory factor analyses, internal-consistency analyses, group comparisons, and hierarchical linear regression were performed. Results The mean scores were 3.95 ± 0.74 for I&E attitude, 3.37 ± 0.68 for self-reported competency, and 2.68 ± 0.90 for participation frequency. Exploratory factor analysis supported a two-factor attitude–self-reported-competency structure that explained 72.2% of the variance, and confirmatory factor analysis showed acceptable-to-good fit (CFI = 0.994, TLI = 0.993, RMSEA = 0.070, SRMR = 0.072). Students with prior I&E experience had higher self-reported competency scores than those without experience (3.47 ± 0.70 vs. 3.29 ± 0.65, p < 0.001), whereas the seven-item attitude scores did not differ significantly ( p = 0.058). In the fully adjusted model, attitude (standardized β = 0.481, p < 0.001) and participation frequency (standardized β = 0.315, p < 0.001) were each associated with self-reported competency. The final model explained 41.8% of the variance, whereas the binary prior-experience variable was not associated with self-reported competency (standardized β = 0.005, p = 0.882). Conclusion Students reported attitude scores above the scale midpoint, participation-frequency scores below the midpoint, and self-reported competency scores slightly above the midpoint. More favorable attitudes and more frequent participation were associated with higher self-reported competency scores; however, the cross-sectional design does not permit causal inference.